Statistical estimation of the regions of Belarus competitiveness dynamics based on integral indicator - Khatskevich, Guennadi A.; Lialikava, Valiantsina I.; Laneuskaya, Hanna A. (Journal of the Belarusian State University. Economics, 2018)
The state program of innovative development of the Republic of Belarus for 2016 –2020 as one of priorities of social and economic development has defined the balanced regional development. The analysis of dynamics of the Belarus regions and the Minsk city for 2011–2015 on competitiveness on the basis of panel data is carried out in the work. The system of indicators which reflects competitiveness of the studied regions consists of five blocks is constructed: quality of the population, standard of living of the population, quality of the social sphere, quality of the environment, investment attractiveness. Data from official statistical collections of the Republic of Belarus are used in a research. Cost indexes for various years are brought to a comparable form by division into the budget of a living wage of able-bodied population into the end of the year. By means of the factor analysis the integrated indicator is constructed. Expert estimates werenʼt used. The rating of regions for 2011–2015 is constructed. Dynamics of competitiveness of regions within one year and each region during studying is analyzed. At the same time all initial indicators are sorted by extent of their influence on rating. Major factors of differentiation for regions for the considered period are revealed: quality of the population, investment attractiveness, standard of living of the population. The tendency of decrease in an integrated indicator of competitiveness of regions, except for the Minsk city and the Minsk region is revealed.
Keywords: the competitiveness of the region; the quality of life of the population; investment attractiveness; the integrated indicator; factor analysis; panel data